Circulating Irisin in Children and Adolescents With Prader-Willi Syndrome: Relation With Glucose Metabolism - Mai, Stefania; Fintini, Danilo; Mele, Chiara; Convertino, Alessio; Bocchini, Sarah; Grugni, Graziano; Aimaretti, Gianluca; Vietti, Roberta; Scacchi, Massimo; Crinò, Antonino; Marzullo, Paolo (Frontiers in Endocrinology, 2022)
Irisin is a myokine involved in the browning of white adipose tissue and regulation of energy expenditure, glucose homeostasis and insulin sensitivity. Debated evidence exists on the metabolic role played by irisin in children with overweight or obesity, while few information exist in children with Prader Willi Syndrome (PWS), a condition genetically prone to obesity. Here we assessed serum irisin in relation to the metabolic profile and body composition in children and adolescents with and without PWS. In 25 PWS subjects (age 6.6-17.8y; BMI SDS 2.5±0.3) and 25 age, and BMI-matched controls (age 6.8-18.0y; BMI SDS, 2.8±0.1) we assessed irisin levels and metabolic profile inclusive of OGTT, and body composition by DXA. In PWS, we recorded lower levels of FFM (p <0.05), fasting (p<0.0001) and 2h post-OGTT insulin (p<0.05) and lower insulin resistance as expressed by HOMA-IR (p<0.0001). Irisin levels were significantly lower in PWS group than in controls with common obesity (p<0.05). In univariate correlation analysis, positive associations linked irisin to insulin OGTT0 (p<0.05), insulin OGTT120 (p<0.005), HOMA-IR (p<0.05) and fasting C-peptide (p<0.05). In stepwise multivariable regression analysis, irisin levels were independently predicted by insulin OGTT120. These results suggest a link between irisin levels and insulin sensitivity in two divergent models of obesity.